Cassava entomology and acarology - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1992)
Results are presented of entomology and acarology research conducted in cassava to develop effective, cost-efficient, environmentally sound crop protection methodologies which stabilize production and thus eliminate the need for pesticide use. Emphasis was made on biological control, host plant resistance, and agricultural practices. Pests cited include Phenacoccus manihoti, P. herreni, Pseudococcus mandio, Erinnyis ello, Bemisia tabaci, B. tuberculata, Aleurotrachelus socialis, Trialeurodes variabilis, Cyrtomenus bergi, and Amblystira machalana. Among mites are Mononychellus tanajoa and Oligonychus gossypii. Information is also provided on the geographical distribution of pests, geographic association among mites, phytoseiid diet analysis (acarine food types, nonacarine food types, cannibalism), and alternative biological control agents. (CIAT)